2021
DOI: 10.1590/0001-3765202120191402
|View full text |Cite
|
Sign up to set email alerts
|

Beta-1,3-glucanase inhibitors in Brazilian brown seaweed

Abstract: Beta-1,3-glucanases are enzymes that hydrolyze beta-1,3-glucans, and they are essential for the metabolism of seaweed, plants and fungi. These enzymes also participate in the digestion of herbivore and fungivore animals. Because of the importance of these enzymes in insects, beta-1,3-glucanase inhibitors may be used for the development of new control strategies against agricultural pests and disease vectors. Beta-1,3-glucanase inhibitors have been described in the brown seaweed Laminaria cichorioides, but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The brown algae species Lobophora sp., Colpomenia sinuosa (Mertens ex Roth) Derbès & Solier, Padina gymnospora (Kützing) Sonder, and Dictyota sp. inhibit the activity of digestive enzymes like catalase, superoxide dismutase, and glutathione peroxidase [ 27 ]. The literature has also revealed that tannins decrease the activity of the enzymes involved in detoxification, acetylcholine esterase, digestion, and protein synthesis in insects [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brown algae species Lobophora sp., Colpomenia sinuosa (Mertens ex Roth) Derbès & Solier, Padina gymnospora (Kützing) Sonder, and Dictyota sp. inhibit the activity of digestive enzymes like catalase, superoxide dismutase, and glutathione peroxidase [ 27 ]. The literature has also revealed that tannins decrease the activity of the enzymes involved in detoxification, acetylcholine esterase, digestion, and protein synthesis in insects [ 28 ].…”
Section: Introductionmentioning
confidence: 99%